Analysis of The Implementation of The Education Council Program in Advancing Education in Kendari City - anidi saidi (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
This study aims to describe the implementation of the program implemented by the Education Council in advancing education in Kendari City in January - June 2020. This research is a qualitative descriptive study, with data collection techniques used, namely observation, interviews, and documentation. The data analysis technique this study uses is the Miles & Huberman analysis technique; namely, the analysis consists of three streams of activities that co-occur: data reduction, data presentation, and conclusion drawing/verification. The study results show that the Education Council's January-June 2020 program to advance education includes: (a) assistance in the implementation of education; and (b) strengthening the institutional relationship of the education board with interested parties.